Amy Fromme: capstone - Fromme, Amy, artist (Colorado State University. Libraries, 2023)
The artist's statement: My artistic practice fuses my roles as both an observer and a translator, providing an opportunity for a conversation between what can be studied and how to best use materials to imitate, alter, and reconceptualize the observable world. I am constantly absorbing facets of the world around me, be it by reflection of body language, inquisition of the diverse qualities of the natural world, or delving into the meditative attributes that musical synesthesia can endow. Intentional observation is the root of my motive to create. My production begins by transforming observational interpretations into an inventory of ideas. My creative index is then further refined through my relationship with music. I often experience synesthesia, which allows a space for auditory stimuli to work in collaboration with visual imaginations. This phenomena motivates me to translate my sensory experiences into sculptural artwork. Once I have honed a concept, I assign materials that will honor my idea. To represent a gestural theme, I may select a steel rod as an armature. While a steel rod may appear rigid, the slightest bend creates a possibility for an individualized expression. Each material decision plays a role in the final product of my work, bridging the gap between ideation and formation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture